MENGELOLA KEUANGAN SEKOLAH - Subur Karyatun (Jurnal Ilmu dan Budaya, 2016)
Schools constitutes social non-profit entities that become a service industry, involving the inflow and outflow of money. In financial management, schools are also obliged to adhere to the principles of transparency and accountability. The paper discusses the need for applying such principles by financial management in schools. It is the finding of the writer that there are issues that hinder good financial management in schools. The issues are less effective practices and lack of discipline as indicative of poor leadership. The suggestion made is that effectiveleadership should be present in order to achieve good financial management I schools.